A patient-centered research agenda for the care of the acutely ill older patient - Wald, Heidi L. (J Hosp Med, 2015)
Hospitalists and others acute care providers are limited by gaps in evidence addressing the needs of the acutely ill older adult population. The Society of Hospital Medicine (SHM) sponsored the Acute Care of Older Patients (ACOP) Priority Setting Partnership to develop a research agenda focused on bridging this gap. Informed by the Patient-Centered Outcomes Research Institute (PCORI) framework for identification and prioritization of research areas, we adapted a methodology developed by the James Lind Alliance to engage diverse stakeholders in the research agenda setting process. The work of the Partnership proceeded through four steps: convening, consulting, collating, and prioritizing. First, the steering committee convened a Partnership of 18 stakeholder organizations in May 2013. Next, stakeholder organizations surveyed members to identify important unanswered questions in the acute care of older persons, receiving 1299 responses from 580 individuals. Finally, an extensive and structured process of collation and prioritization resulted in a final list of ten research questions in the following areas: advanced care planning, care transitions, delirium, dementia, depression, medications, models of care, physical function, surgery, and training. With the changing demographics of the hospitalized population, a workforce with limited geriatrics training, and gaps in evidence to inform clinical decision-making for acutely ill older patients, the identified research questions deserve the highest priority in directing future research efforts to improve care for the older hospitalized patient and enrich training.